2021
DOI: 10.3390/ijerph18052307
|View full text |Cite
|
Sign up to set email alerts
|

Could Physical Activity Have any Role in Cardiovascular Disease Prevention in Prisoners? A Systematic Review

Abstract: More than 10.74 million people are currently held in penal institutions worldwide. Moreover, there is also evidence that the percentage of elder and female prisoners has been consistently growing. Cardiovascular diseases are the leading cause of death worldwide. Exercise training and physical activity help to prevent both primary and secondary cardiovascular events. Data on the influence of physical activity on the well-being in prison population is scarce. Here, we discussed, in a systematic review, the gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 67 publications
(102 reference statements)
1
9
0
Order By: Relevance
“…There was also an increase in strength training self-efficacy ( t = −8.33, p < 0.001, Cohen's d = 1.36) from baseline ( M = 19.28, SD = 4.78) to posttest ( M = 24.67, SD = 2.96) in line with our prediction. These findings are in line with evidence from the previous Hercules program for adolescents (Sagoe et al, 2016 ) as well as from previous physical activity interventions in prisons (Mohan et al, 2018 ; Sanchez-Lastra et al, 2019 ; Papa et al, 2021 ).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…There was also an increase in strength training self-efficacy ( t = −8.33, p < 0.001, Cohen's d = 1.36) from baseline ( M = 19.28, SD = 4.78) to posttest ( M = 24.67, SD = 2.96) in line with our prediction. These findings are in line with evidence from the previous Hercules program for adolescents (Sagoe et al, 2016 ) as well as from previous physical activity interventions in prisons (Mohan et al, 2018 ; Sanchez-Lastra et al, 2019 ; Papa et al, 2021 ).…”
Section: Resultssupporting
confidence: 89%
“…In particular, self-ratings of physical strength are relative (“compared with my peers”) rather than absolute and are therefore probably affected by rank order fluctuation, especially considering the hierarchical structure of prison society (Ugelvik, 2014 ; Kreager et al, 2017 ) as noted previously. Also, although the sample size appears low, it is justified by power analysis and is equivalent to the preponderance of samples from similar interventions on this topic (Mohan et al, 2018 ; Legrand et al, 2020 ; Pralong et al, 2020 ; Psychou et al, 2020 ; Papa et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…After a complete inspection and confidence in the vaccine, it will be recommended by the SAGE when and how it should be used. 18 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is a dire need to devise special measures at the international level for the old age prisoners, 18 as studies reported that due to long-term and chronic disease, the aging process of the prisoners is faster than their associates on the outside of the prison. 19 Thus, the current study highlighted the need for old-age prisons priority treatment based on multiple reasons.…”
Section: Introductionmentioning
confidence: 99%
“…substance use and mental health) and the public’s ideas about what prisoners deserve. It seems worth remarking that one frequent argument in the more robust body of interventional research that addresses the physical health of incarcerated men is that improving physical health is a foundation for (rather than an embellishment on or a supplement to) addressing both substance abuse and mental health conditions (Sanchez-Lastra et al , 2019; Papa et al , 2021; O’Toole et al , 2018). Increasing physical activity as a basis for improving the all-round health of persons who are incarcerated has been a focus of numerous international studies, many conducted in countries falling under mandates of international bodies requiring access to exercise (Brosens et al , 2017) Some of these include studies in Australia, Canada, England, Ireland, Italy, Spain and Wales (Thompson et al , 2020; Cashin et al , 2008; Elwood Martin et al , 2013; Meek and Lewis, 2012; Mannocci et al , 2015; Pérez-Moreno et al , 2007).…”
Section: Discussionmentioning
confidence: 99%